Peningkatan Prestasi Belajar Materi Logaritma melalui Pemahaman Konsep dalam Pembelajaran Matematika pada Siswa Kelas X TKJ1 SMK Negeri 1 Sawit Kabupaten Boyolali Semester Gasal Tahun Pelajaran 2011/2012 - Sutanto Sutanto (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2015)
The research was inspired by the unsatisfactory attainment of students on understanding concept implementation (learning mastery) through logaritm at class X students TKJI SMK Negeri Sawit Boyolali Regency odd semester 2011/2012. The research aim at describing the optimalisation of logarithm subject mastery. The subject and data source of the research are 39 students of class X TKJI SMK Negeri Sawit Boyolali Regency by using obseravtion documentation and test. The data analysis uses critical and comparative data analysis. The completion indicator used is 69. The research uses a cycle procedure. The findings from cycle I, II and II show that there is a progress motivation of the students in the class. In Cycle I 67 average, cycle II 83 and cycle III 92. This shows the significant increase on the motivation of the students from cycle I until cycle III